Air dispersion modeling of SOx and NOx emissions from a petroleum refinery plant - Carrillo, Jan-Michael Y. (2003)
Dispersion modeling of SOx and NOx emissions from a petroleum refinery plant was performed using United States Environmental Protection Agency (USEPA) recommended Air Dispersion Modeling software. Monthly emissions data, terrain information and weather data were obtained and used to create a one year study of the dispersion of NOx and SOxs in the vicinity of the Refinery. Ambient air concentration contour maps for SOx and NOx were created to illustrate the dispersion of these pollutants on a monthly basis. Chronological NOx and SOx emissions were obtained indirectly from calculations based on first principle modeling and data from furnace and boiler online Oxygen analyzers and refinery fuel flow meters. Weather data were gathered from the refinery's local weather station and other weather data requirements such as mixing height and stability were calculated based on mathematical correlations. Terrain data from the refinery's pilot plan, aerial photographs, elevation contour maps and field survey were also incorporated into the model.
The dispersion modeling had shown that seasonal monsoon winds impacted on the dispersion of the SOx and NOx inland and into some of the populated ares. The modeling determined the locations where the highest concentrations of SOx and NOx occurred and it showed that values go beyond the Ambient Air Quality Guideline Values for SOx as prescribed by the Philippine Clean Air Act at 50 m above sea level. The model reported maximum 24-hour averaging period of SOx values ranging from 800 to 1360 micrograms per normal cubic meter, and maximum 24-hr averaging period of NOx values ranging from 2.0 to 3.6 microgram per normal cubic meter.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Air quality -- Mathematical models. -- Philippines -- Bataan; Air quality management -- Philippines -- Bataan; Dispersion -- Mathematical models; Sulphur oxides -- Environmental aspects -- Philippines -- Bataan; Nitrogen oxides -- Environmental aspects -- Philippines -- Bataan